Fablehaven 2 : Rise of the evening star - Mull, Brandon, 1974- (New York : Aladdin Paperbacks, 2008)
Kendra and Seth find themselves in the midst of a battle between good and evil when they visit their grandparents' estate and discover that it is a sanctuary for magical creatures.
Kirkus Review
Teacher Librarian
Kirkus Review, April 2007
Teacher Librarian, December 2007
5-8
Keywords: Brothers and sisters -- Juvenile fiction; Grandparents -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Fiction; Grandparents -- Fiction; Magic -- Fiction; Grandparents -- Fiction; Magic -- Fiction; Siblings -- Fiction